Aditivos: clasificación y uso en alimentos - Vásquez Ruiz, Arnold Anthony (2022)
Food additives are non-nutritive substances or compounds that are intentionally added to the food for a different purpose in its manufacturing, preparation, transformation, packaging, transportation or storage process, in order to transform them into safer foods, protecting them from changes. environmental, bacteria and preventing its oxidation beforehand, thus improving its flavor, consistency and texture. The widespread use that the food industry makes of additives forces it to establish control mechanisms that regulate their correct use and that verify their results in terms of providing added value to the consumer. And they have a regulation in which they are classified and that regulates their use. In PERU, the body in charge of compliance with these regulations is the General Directorate of Environmental Health and Food Safety "DIGESA", by intervention of the CODEX ALIMENTARIUS. And in turn, food additives are an important tool in the food industry. Its use obeys criteria and sanitary, socioeconomic and technological reasons. These substances are regularly regulated and evaluated by different competent bodies, both internationally and nationally, who authorize their use by meeting the established safety and innocuousness requirements. Despite this, there is distrust among consumers due to the possible health risks that its use entails.